2018
DOI: 10.1029/2018tc005011
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis on the Stress Field and Seismic Anisotropy in Eastern Tibet

Abstract: Widespread rotations of maximum compressive stress in the upper crust are revealed in eastern Tibet by the focal mechanism stress inversion technique. Because of the good correlation with locations of folds, anticlines, and mountains in the region, the upper crustal stress variation is related to the lateral displacement of upper crust. To compare deformations in upper crust and upper mantle, we use SKS/SKKS splitting measurements to investigate the seismic anisotropy in eastern Tibet. The fast polarization di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…The teleseismic P wave receiver functions (Langston, ) used in this study were extracted by He et al () and Yang et al () from 110 broadband seismic stations that were densely deployed at different times in the LMS and Sichuan Basin regions (Figure ). These stations include the Western Sichuan array (2006–2009), the Lushan Scientific Investigation network (2013–2015), the Seismic Gap Investigation network (2015–2016), and permanent stations of the digital seismic network of Sichuan Province (2012–2014).…”
Section: Methodsmentioning
confidence: 99%
“…The teleseismic P wave receiver functions (Langston, ) used in this study were extracted by He et al () and Yang et al () from 110 broadband seismic stations that were densely deployed at different times in the LMS and Sichuan Basin regions (Figure ). These stations include the Western Sichuan array (2006–2009), the Lushan Scientific Investigation network (2013–2015), the Seismic Gap Investigation network (2015–2016), and permanent stations of the digital seismic network of Sichuan Province (2012–2014).…”
Section: Methodsmentioning
confidence: 99%
“…Given these achievements, the debate on the deformation mechanism in this region still exists. For example, joint analysis of GPS and SKS/SKKS splitting results shows that deformations in the crust and mantle are largely coupled in the eastern Tibetan Plateau, which is inconsistent with the predictions of the lower crust flow model (Chang et al, 2015; León Soto et al, 2012; Sol et al, 2007; Wang et al, 2008; Yang et al, 2018). On the other hand, based on anisotropies from Pms phases, some studies (Kong et al, 2016; Sun et al, 2012; Sun et al, 2015; Zheng et al, 2018) have suggested the existence of a lower crust flow in the region.…”
Section: Introductionmentioning
confidence: 93%
“…Many techniques have been used to estimate radial and azimuthal anisotropy. Shear wave splitting is often used to estimate crust polarization anisotropy (Pms waves) and mantle radial anisotropy (SKS, SKKS) and has yielded numerous results (Chang et al, 2015; Chen et al, 2013; Crampin, 1985; Kong et al, 2018; Yang et al, 2018; Zheng et al, 2018; etc.). Shear wave splitting near earthquakes represents upper‐middle crust anisotropy, but they are easily disturbed by the complexities of sources, multipath, and scattering (Lai et al, 2006); SKS splitting can yield stable anisotropies and is often attributed to the upper mantle anisotropic medium.…”
Section: Discussionmentioning
confidence: 99%
“…The fast orientation of anisotropies from XKS and Pms, the direction of maximum compressive stresses (Yang et al, 2018), and surface movement detected by GPS are aligned at nearly NW‐SE, and they are systematically different from fault strikes and orogenic belts. The surface movement direction (Zhao et al, 2015) and maximum compressive stresses direction (Yang et al, 2017, 2018) inverted by focal mechanisms carry information on current tectonic movement, and they may not be affected by ancient tectonic events as much as the fast orientation of anisotropies determined by the WG method. In addition, considering the difference in periods observed between the surface wave (long periods) and S wave (short periods), the anisotropy of the long‐period surface wave may be more sensitive to macroscopic structures created by the deformation of the lithosphere while short‐period S wave splitting is more sensitive to local stresses or the microscopic structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation